Use of Lime as Filler in Cold Mix Asphalt - Jain S.; Singh B.; Saboo N. (My University, 2025)
Considerable advantages could be attained if cold bituminous emulsion mixes (CBEM’s) show superior engineering properties than hot mix asphalt (HMA). Particularly, cold mix asphalt (CMA) does not require any heating at the time of manufacturing and laying process. This reduces emission of harmful greenhouse gases considerably and makes it economical also. Despite of these advantages, CMA has limited utilisation in the field because of issues such as poor performance, lower moisture resistance. So, the present paper focuses on improving the performance of CMA with filler replacement. Lime is used as filler in this study to improve the mechanical properties of CMA. Stone dust was replaced with lime in the proportion of 1, 2, 3% dry weight of aggregate in mixture. Marshall stability retained stability and indirect tensile strength were performed. Results obtained from these tests were compared, and lime was found to be improving CMA properties considerably. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.